Effects of materials selection on injection moulding parameters using moldflow simulation software - Mohd Nazri, Ismail (2009)
This dissertation deals with the effects of material selection on injection moulding parameters using Moldflow simulation software. The objective of this dissertation is to define suitable material in producing plastic product (book tray) in term of Profit. The dissertation also describes the finite element analysis techniques to know the effect of cycle time to production cost and reduce the cost in define the material selection using manual method. Eight plastic materials were studied in this dissertation which commonly used in industrial. The three-dimensional solid modelling of plastic product (book tray) was developed using the computer-aided drawing software. The dimension of product based on the actual product mould. The three-dimensional solid modelling of plastic product will import to the computer aided engineering software. The computer aided engineering software was then performed is using Moldflow (MPI) simulation software. The computer aided engineering model of product was analyzed using injection flow analysis. The analysis need to repeat three time for each eight material. Finally, the average value of cooling time (s), filling time (s), and initial injection time (s) obtained from the analysis. From those parameters, the cycle time of product producing can be calculated for each eight material. The cycle time can relate to the production capacity, product cost and profit. From that comparison, the best material for plastic product (book tray) can be selected and also can know the effect of cycle time only on processing cost. By using this analysis method also can reduce the cost in define the material selection for plastic product using manual method.